2016
DOI: 10.1039/c6ob01282e
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acid-catalyzed regioselective reactions of 2-indolylmethanols with cyclic enaminone and anhydride leading to C3-functionalized indole derivatives

Abstract: An abnormal regioselective substitution of 2-indolylmethanols with nucleophiles such as cyclic enaminone and cyclic anhydride has been established in the presence of Brønsted acid, which efficiently afforded C3-functionalized indole derivatives with structural diversity in high yield and regiospecificity (40 examples, up to 99% yield). Using this approach, the reactivity of the C3-position of the indole was switched from nucleophilic to electrophilic, which could serve as an "umpolung" strategy in organic synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Indolylmethanols have proven to be versatile reactants for enantioselective synthesis of chiral indole derivatives because they are easily transformed into carbocation, vinyliminium, and delocalized cation intermediates under the catalysis of an acid . In our ongoing project to develop indolylmethanol‐involved enantioselective transformations, we found that the C3‐position of 2‐indolylmethanols displayed unusual electrophilicity, which could be attacked by nucleophiles (Nu) to accomplish organocatalytic indole–Nu couplings . We conceived that, if a large aromatic Nu was employed in the reaction with 2‐indolylmethanols bearing two bulky R substituents in the presence of a chiral Brønsted acid (B‐H*), an axially chiral indole‐aryl framework would be constructed because of the steric congestion around the indole‐aryl axis (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Indolylmethanols have proven to be versatile reactants for enantioselective synthesis of chiral indole derivatives because they are easily transformed into carbocation, vinyliminium, and delocalized cation intermediates under the catalysis of an acid . In our ongoing project to develop indolylmethanol‐involved enantioselective transformations, we found that the C3‐position of 2‐indolylmethanols displayed unusual electrophilicity, which could be attacked by nucleophiles (Nu) to accomplish organocatalytic indole–Nu couplings . We conceived that, if a large aromatic Nu was employed in the reaction with 2‐indolylmethanols bearing two bulky R substituents in the presence of a chiral Brønsted acid (B‐H*), an axially chiral indole‐aryl framework would be constructed because of the steric congestion around the indole‐aryl axis (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…[18] This strategy was devisedo nt he basis of their discoveryo ft he umpolung reactivity of 2-indolylmethanols. [13,25,26] Namely,t he reactivity of the indole C3 positioni n2 -indolylmethanols was changed from its known nucleophilicityt oe lectrophilicity, which had scarcely been recognized (Scheme 6a). Based on this uniquer eactivity,t hey proposed that using ab ulky aryl nucleophile (Nu-H)i nt his reactionw ith 2-indolylmethanols would produce an axially chiral arylindole framework bearing a CÀCaxis because of the steric congestion around the axis.…”
Section: Axially Chiral Arylindolesmentioning
confidence: 99%
“…By the end of 2016 (online date of publication), Shi, Li and co‐workers demonstrated the first catalytic asymmetric construction of axially chiral arylindoles bearing a stereogenic C−C axis via the strategy of coupling an indole ring with another ring [18] . This strategy was devised on the basis of their discovery of the umpolung reactivity of 2‐indolylmethanols [13, 25, 26] . Namely, the reactivity of the indole C3 position in 2‐indolylmethanols was changed from its known nucleophilicity to electrophilicity, which had scarcely been recognized (Scheme 6 a).…”
Section: Catalytic Asymmetric Construction Of Axially Chiral Indole‐bmentioning
confidence: 99%
“…Tertiary 2‐indolylmethanols 33 react with cyclic enaminones 34 in the presence of pentafluorobenzoic acid leading to compounds 36 showing a marked preference for C‐3 ring addition (Scheme ) . The steric hindrance around the exocyclic electrophilic site is probably responsible for the observed regioselectivity in these reactions.…”
Section: Enol Ethers and Azaenolsmentioning
confidence: 99%